2021
DOI: 10.1002/ijop.12796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms of anxiety disorders as predictors of political attitudes: A prospective cohort study

Abstract: C onservative political ideologies have been suggested to correlate with elevated sensitivity to threat. However, it is unclear whether the associations between threat sensitivity and political attitudes can be observed with clinical measures of mental health. We examined how anxiety disorders predicted attitudes on several political issues. Participants were 7253 individuals from the 1958 British Birth Cohort study. Symptoms of generalised anxiety disorder, phobia and panic were assessed in a clinical intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The latter studies, not surprisingly, have focused more on political traits, and consistently found political orientation, interest, and engagement to be positive correlates with political anxiety (e.g., Smith, 2022;Smith et al, 2023). The impact of such political variables on general anxiety is largely unknown, though rates of depression have been reported to be higher among liberals than conservatives (e.g., Gimbrone et al, 2022), and a study by Helminen et al (2022) found that in Great Britain those with left-leaning attitudes on several issues (e.g., inequality, concern for the environment) had higher anxiety scores than those with right-leaning attitudes.…”
Section: Correlates Of Political and General Anxietymentioning
confidence: 96%
“…The latter studies, not surprisingly, have focused more on political traits, and consistently found political orientation, interest, and engagement to be positive correlates with political anxiety (e.g., Smith, 2022;Smith et al, 2023). The impact of such political variables on general anxiety is largely unknown, though rates of depression have been reported to be higher among liberals than conservatives (e.g., Gimbrone et al, 2022), and a study by Helminen et al (2022) found that in Great Britain those with left-leaning attitudes on several issues (e.g., inequality, concern for the environment) had higher anxiety scores than those with right-leaning attitudes.…”
Section: Correlates Of Political and General Anxietymentioning
confidence: 96%
“…Generally, it is assumed in political science that anxiety increases both the desire for information and the active search for it (Albertson and Gadarian, 2015). In sum, fear and anxiety are both emotions characterized by negative valence that arise in reaction to threat, yet they have a partially different neurobiological basis and may result in different responses to different threats 1 (Helminen et al, 2022). Although fear and anxiety represent distinct emotional experiences for the recipient, we use fear as an umbrella term for the current purpose.…”
Section: From Fear To Hostility: the Psychological And Political Dime...mentioning
confidence: 99%
“…It remains unclear in the extant literature the precise psychological, neurobiological, and contextual factors that differentiate social ideology from economic ideology, and future research would do well to interrogate these relationships. In particular, future research should aim to explain why perceiving negative stimuli as more salient is sometimes associated with social conservatism (e.g., Shook & Fazio, 2009) and other times economic liberalism (e.g., Helminen et al., 2022; Panish & Delton, 2023). This could be done, for example, by showing people a series of equally negatively‐valenced images while varying the specific content (e.g., poverty, military threats, natural disasters, etc.)…”
Section: Recommendations and Future Directionsmentioning
confidence: 99%
“…In accordance with this perspective, social conservatism predicts poorer performance on behavioral measures of cognitive updating (Costello et al., 2023), whereas conservatives outperform liberals in tasks requiring perseverance and consistency (Buechner et al., 2021). Meanwhile, there is growing evidence that the concern with suffering and injustice that characterizes economic liberalism is motivated, in part, by sensitivity to anxiety that increases anticipation of and aversion to harm (Bondü & Inerle, 2020; Helminen et al., 2022; Panish & Delton, 2023).…”
Section: The Anterior Cingulate Cortex: Conflict Monitoring and Emoti...mentioning
confidence: 99%